Character Education in Islamic Thought: A Comparative Study of Al-Miskawaih and Al-Ghazali - Alwy Ahmed Mohamed; Muk Andhim (Demagogi: Journal of Social Sciences, Economics and Education, 2026)
Character education has long been a central concern in Islamic intellectual tradition, particularly in the works of classical Muslim scholars who emphasised the development of moral virtues and ethical behaviour. This study examines the concept of character education in the thought of Abū ʿAlī Aḥmad ibn Muḥammad ibn Yaʿqūb Miskawayh and Abu Hamid al-Ghazali, two prominent Muslim thinkers who significantly contributed to Islamic ethical philosophy. The research aims to analyse and compare their perspectives on the formation of moral character and the role of education in cultivating virtuous individuals. Using a qualitative library research method, this study examines primary texts such as Tahdhib al-Akhlaq by Al-Miskawaih and Ihya Ulum al-Din by Al-Ghazali, as well as relevant secondary literature. The findings reveal that Al-Miskawaih emphasises a rational and philosophical approach to moral education, highlighting the importance of intellectual discipline and balance among human faculties to achieve virtue. In contrast, Al-Ghazali focuses more on spiritual purification, emphasising the role of faith, self-discipline, and religious practices in shaping moral character. Despite their methodological differences, both scholars share a common goal of guiding individuals toward moral excellence and social harmony. This study concludes that integrating their perspectives can provide valuable insights for contemporary Islamic education, particularly in developing character-based curricula that combine intellectual development with spiritual and ethical formation.